Phosphoglycerate mutase 5 exacerbates liver ischemia–reperfusion injury by activating mitochondrial fission - Hongwei Tang; Qiwen Yu; Xu Chen; Jiakai Zhang; Danfeng Guo; Wenzhi Guo; Shuijun Zhang; Xiaoyi Shi (Scientific Reports, 2024)
Abstract Although the death of hepatocytes is a crucial trigger of liver ischemia–reperfusion (I/R) injury, the regulation of liver I/R-induced hepatocyte death is still poorly understood. Phosphoglycerate mutase 5 (PGAM5), a mitochondrial Serine/Threonine protein phosphatase, regulates mitochondrial dynamics and is involved in the process of both apoptosis and necrotic. However, it is still unclear what role PGAM5 plays in the death of hepatocytes induced by I/R. Using a PGAM5-silence mice model, we investigated the role of PGAM5 in liver I/R injury and its relevant molecular mechanisms. Our data showed that PGAM5 was highly expressed in mice with liver I/R injury. Silence of PGAM5 could decrease I/R-induced hepatocyte death in mice. In subcellular levels, the silence of PGAM5 could restore mitochondrial membrane potential, increase mitochondrial DNA copy number and transcription levels, inhibit ROS generation, and prevent I/R-induced opening of abnormal mPTP. As for the molecular mechanisms, we indicated that the silence of PGAM5 could inhibit Drp1(S616) phosphorylation, leading to a partial reduction of mitochondrial fission. In addition, Mdivi-1 could inhibit mitochondrial fission, decrease hepatocyte death, and attenuate liver I/R injury in mice. In conclusion, our data reveal the molecular mechanism of PGAM5 in driving hepatocyte death through activating mitochondrial fission in liver I/R injury.